Managing Cold Temperature and Brittle Fracture Hazards in Pressure Vessels - Benac, Daniel J.; Cherolis, Nicholas; Wood, David (Journal of failure analysis and prevention, 2016)
Brittle fractures of pressure vessels can be both catastrophic and costly. The intent of this article is to provide guidance in avoiding such failures by identifying some of the causes for cold embrittlement hazards and brittle fracture in pressure vessels. Selected examples will help illustrate the main factors that contribute to brittle fracture, through identifying brittle fracture features, and demonstrating the importance of coordination of materials and potential operating condition. This article also discusses how to assess existing equipment pressure vessels subject to cold conditions and brittle fracture concerns using the guidelines of API 579-1/ASME FFS-1, Part 3.